CAREER MANAGEMENT IN MANUFACTURING SECTOR WITH REFERENCE TO SELECT INDUSTRIES IN MYSORE DISTRICT- KARNATAKA - S, Mahesh A.; P, Somashekar; Ramanathan, K.V. (International Journal of Psychosocial Rehabilitation, 2020)
Career management is the backbone both from the organization and from the employee’s perspective. Effective career management practices help organizations to reach the desired objective, set goals for the individuals, fulfills one’s personal desire, maintain work life balance. Effective career management practices help in retaining the talent who makes their valuable contribution, more productive workforce, lower employee turnover, high customer satisfaction rates. This has made the researcher to study career management practices in the area of manufacturing sector which aims at understanding the prevailing career management practices and how effectively it has managed. Hence career management in manufacturing sector has become a subject of prime importance. Effective career management practices increase the productivity of employees and improve the various levels of workplace diversity competencies for organizational excellence.